Idiopathic cerebellar ataxia of late onset: natural history and MRI morphology. Issue 4 (April 1990) - Klockgether, T; Schroth, G; Diener, H C; Dichgans, J
Abstract : Twenty eight patients with the clinical diagnosis of idiopathic late onset cerebellar ataxia were examined clinically and by magnetic resonance imaging (MRI) or computed tomography (CT). In addition, the clinical records of all patients were analysed retrospectively. On the basis of their clinical presentation they were subdivided into patients with a pure cerebellar syndrome (n = 9) and patients with a cerebellar syndrome and additional non-cerebellar symptoms (n = 13). No attempts were made to classify patients with a disease duration of less than four years (n = 6) because the retrospective analysis showed that the disease started almost invariably with a pure cerebellar syndrome and additional symptoms came later. Patients with a lasting pure cerebellar syndrome had a significantly better prognosis than patients with additional non-cerebellar involvement (annual progression rate rate: 0.40 versus 0.80). Calculated median lifetime from onset of symptoms was 20.7 years in patients with a pure cerebellar syndrome and 7.7 years in patients with additional non-cerebellar symptoms. Among the latter, disease progression was faster the earlier non-cerebellar symptoms occurred. All of them presented with Parkinsonian symptoms, whereas bulbar symptoms, vertical gaze paresis, pyramidal deficits, dementia and urinary incontinence were encountered less frequently. MRI or CT showed cerebellar atrophy without apparent involvement of brainstem structures in all patients with a pure cerebellar syndrome suggesting the diagnosis of cerebellar cortical atrophy (CA). The majority of the patients with additional non-cerebellar symptoms had evidence of an atrophy of the cerebellum and the brainstem suggesting the presence of olivo-ponto-cerebellar atrophy (OPCA). In two of them, however, MRI morphology was not compatible with the diagnosis of OPCA.